Gastroesophageal reflux disease: A clinical overview for primary care physicians. Issue 1 (March 2018) - Pandit, Sudha; Boktor, Moheb; Alexander, Jonathan S.; Becker, Felix; Morris, James
Abstract: Objective: GERD is among the most common outpatient disease processes encountered by clinicians on a daily basis. This review provides insights about how to approach GERD in terms of disease management and treatment. Methods: Review articles were searched using PUBMED and MEDLINE using criteria that included English language articles published in the last 5 years concerning studies carried out only in humans. The key words used in the searches were GERD, PPI, and erosive esophagitis. Recommendations from the American College of Gastroenterology are also included in this manuscript. Results: The search resulted in ∼260 articles. The manuscript brings together and presents the results of recent recommendations from professional societies and recently published review articles on GERD. Conclusion: GERD is one of the most common diagnoses made by gastroenterologists and primary care physicians. It is important to recognize the typical and atypical presentations of GERD. This paper helps primary care physicians understand the disease's pathophysiology, and when, how, and with what to treat GERD before referring patients to gastroenterologists or surgeons.